(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
Brazilian Guidelines to HCV treatment (2007) recommended that the first choice treatment for patients with chronic hepatitis C (CHC) and genotype 2 or 3 is interferon alpha (IFN) plus ribavirin (RBV) for 24 weeks. The aim of this study is compare the cost and effectiveness to Hepatitis C treatment in patients with genotype 2 or 3 of peginterferon alpha (PEG) as the first choice of treatment within PEG for those that do not respond to IFN. The target population is CHC patients with genotype 2 or 3 in Brazil. The interventions are: PEG-SEC (first IFN plus RBV for 24 weeks, after, for non-responders and relapsers subsequently PEG plus RBV for 48 weeks); PEG-FIRST24 (PEG+RBV for 24 weeks). The type of the study is cost-effectiveness analysis. The data sources are: Effectiveness data from meta-analysis conducted on the Brazilian population. Treatment cost from Brazilian micro costing study is converted into USD (2010). The perspective is the Public Health System. The outcome measurements are Sustained Viral Response (SVR) and costs. PEG-FIRST24 (SVR: 87.8%, costs: USD 8,338.27) was more effective and more costly than PEG-SEC (SVR: 79.2%, costs: USD 5,852.99). The sensitivity analyses are: When SVR rates with IFN was less than 30% PEG-FIRST is dominant. On the other hand, when SVR with IFN was more then 75% PEG-SEC is dominant (SVR=88.2% and costs USD 3,753.00). PEG-SEC is also dominant when SVR to PEG24 weeks was less than 54%. In the Brazilian context, PEG-FIRST is more effective and more expensive than PEG-SEC. PEG-SEC could be dominant when rates of IFN therapy are higher than 75% or rates of PEG24 therapy are lower than 54%.